2013
DOI: 10.1177/0009922813493830
|View full text |Cite
|
Sign up to set email alerts
|

Injury/Illness Physician Referral Profile From a Youth University-Sponsored Summer Sport Camp Program

Abstract: Participation at university-sponsored summer sport camps is popular among youth athletes; however, there is a dearth of information to describe the injuries/illnesses experienced by camp participants. Data from a university-sponsored sport camp program from 2008 to 2011 were accessed retrospectively. The sport camp program had approximately 80 camps for 28 sports over 12 weeks annually. Male and female participants were 10 to 17 years old. Athletic trainers maintained medical documentation and provided medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Additionally, 60.1% of all camper injuries in the Healthy Camp Study required off-site medical referrals and treatment. 20 When we 22 described the physician referral profile from our same sport-camp program, we found that only 9.7% of all sport-camp injuries and illnesses required medical referral. Although further research is needed to determine the reasons for the observed differences between our study and the Healthy Camp Study, the results indicate that recreational campers and sport-camp participants have different injury and illness experiences.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, 60.1% of all camper injuries in the Healthy Camp Study required off-site medical referrals and treatment. 20 When we 22 described the physician referral profile from our same sport-camp program, we found that only 9.7% of all sport-camp injuries and illnesses required medical referral. Although further research is needed to determine the reasons for the observed differences between our study and the Healthy Camp Study, the results indicate that recreational campers and sport-camp participants have different injury and illness experiences.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11] These studies, and the guidelines published by the American Academy of Pediatrics, 8,12 commonly exclude adults. Several studies have focused on specialized types of camps or populations of campers (such as persons with disabilities), [13][14][15] limiting the generalizability of findings. The literature on wilderness travel is limited in applicability to summer camps, and recommendations are not generally evidencebased.…”
Section: Introductionmentioning
confidence: 99%